2020
DOI: 10.3390/molecules25173955
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity and Mechanism of Ginger Essential Oil against Escherichia coli and Staphylococcus aureus

Abstract: Though essential oils exhibit antibacterial activity against food pathogens, their underlying mechanism is understudied. We extracted ginger essential oil (GEO) using supercritical CO2 and steam distillation. A chemical composition comparison by GC-MS showed that the main components of the extracted GEOs were zingiberene and α-curcumene. Their antibacterial activity and associated mechanism against Staphylococcus aureus and Escherichia coli were investigated. The diameter of inhibition zone (DIZ) of GEO agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(114 citation statements)
references
References 48 publications
7
92
0
Order By: Relevance
“…In the previous study, we reported the antibacterial activity and mechanism of GEO against E. coli and Staphylococcus aureus [18]. In present research, the polysaccharide chitosan as the polymer matrix was combined with nano-clay montmorillonite and natural active substance GEO to prepare GEO, chitosan, and montmorillonite novel bionanocomposite films.…”
Section: Introductionmentioning
confidence: 92%
“…In the previous study, we reported the antibacterial activity and mechanism of GEO against E. coli and Staphylococcus aureus [18]. In present research, the polysaccharide chitosan as the polymer matrix was combined with nano-clay montmorillonite and natural active substance GEO to prepare GEO, chitosan, and montmorillonite novel bionanocomposite films.…”
Section: Introductionmentioning
confidence: 92%
“…The decrease in membrane potential may be attributed to the structural damage of the cell membrane [23]. Measuring the bacterial membrane potential can be achieved by determining the ratio between fluorescence dye intensities inside and outside the cell [23,24]. The membrane potential-sensitive dye, 3,3 -dipropylthiacarbocyanide iodide (DiSC35) [25][26][27] and bis-oxonol [9] are commonly used to stain the depolarised bacterial cells after exposure to EOs.…”
Section: Membrane Disruption Activities Of Eosmentioning
confidence: 99%
“…Pham et al suggested that terpinen-4-ol that is the main active constituent in Z. rhetsa pericarp EOs had the ability to inhibit stomach and intestine diseases [11]. Some other studies have also shown that essential oils obtained from plants exhibited potential antibacterial and antifungal activities [20][21][22].…”
Section: Antimicrobial Activitymentioning
confidence: 99%